VD_FINDINFO Arrêt / 2021 / 831 vom 21. Dezember 2021 - VD Tribunal cantonal (2021)
REVENU SANS INVALIDITÉ, RHUMATISME, MESURE D'ORDRE PROFESSIONNEL, RENTE ÉCHELONNÉE | 15 LAI, 28 LAI, 17 LPGA, 88a RAI